Tristetraprolin Regulates TH17 Cell Function and Ameliorates DSS-Induced Colitis in Mice - Peng, Hui; Ning, Huan; Wang, Qinghong; Lai, Jinping; Wei, Lin; Stumpo, Deborah J.; Blackshear, Perry J.; Fu, Mingui; Hou, Rong; Hoft, Daniel F.; Liu, Jianguo (Frontiers in Immunology, 2020)
Th17 cells have been extensively investigated in inflammation, autoimmune diseases and cancer. The precise molecular mechanisms for Th17 cell regulation, however, remain elusive, especially regulation at the posttranscriptional level. Tristetraprolin (TTP) is an RNA-binding protein important for degradation of the mRNAs encoding several proinflammatory cytokines. With newly generated T cell-specific TTP conditional knockout mice (CD4CreTTPf/f), we found that aging CD4CreTTPf/f mice displayed an increase of IL-17A in serum and spontaneously developed chronic skin inflammation along with increased effector Th17 cells in the affected skin. TTP inhibited Th17 cell development and function by promoting IL-17A mRNA degradation. In a DSS-induced colitis model, CD4CreTTPf/f mice displayed severe colitis and had more Th17 cells and serum IL-17A compared with WT mice. Furthermore, neutralization of IL-17A reduced the severity of colitis. Our results reveal a new mechanism for regulating Th17 function and Th17-mediated inflammation post-transcriptionally by TTP, and suggest that TTP might be a novel therapeutic target for the treatment of Th17-mediated diseases.